The Role of Organizational Citizenship Behavior as a Mediator in the Relationship between Job Satisfaction and Turnover Intentions (Jurusan Psikologi, Fakultas Ilmu Pendidikan, Universitas Negeri Semarang, 2019)
This study was conducted to investigate the mediating effect of organizational citizenship behavior (OCB) in the relationship between job satisfaction turnover intentions. Drawing on social exchange theory, it is expected that individuals with high job satisfaction, indicated by positive emotions towards aspects of work, will show high levels of OCB by helping their coworkers and the organization, and in turn show low turnover intentions. Data were taken from teachers in an International School in Jakarta (N = 80). Result showed that OCB was found to fully mediate the relationship between job satisfaction and turnover intentions, indicating that all variance of job satisfaction was translated into turnover intentions via OCB.Â Theoretical and practical implications were further discussed.Â